Role of C-Reactive Protein in Deciding Duration of Antibiotic Therapy in Neonatal Septicemia - Sah, Love Kumar; Pareek, Prince; Pan, Atanu; Thapa, Sameera; Garegrat, Reema (Journal of College of Medical Sciences-Nepal, 2021)
Introduction Neonatal septicemia is one of the commonest causes of neonatal morbidity and mortality worldwide. C- Reactive Protein (CRP) is an acute phase reactant that can be expected to fall quickly after efficient elimination of microbial stimulus due to its short half-life. CRP levels may sufficiently reflect the balance between microbes and immune system of the neonate for monitoring the effect of antibiotic treatment and for guiding the duration of antibiotic therapy. Methods A prospective study conducted in ninety neonates admitted with suspected neonatal sepsis during one year in tertiary care hospital in the department of pediatrics, College of Medical Sciences, Bharatpur, Nepal from October 2013 to September 2014. CRP was estimated within 24–72 hours of admission. Then neonates were assigned to one of 3 groups according to CRP levels. Infection unlikely group, infection likely group with two subgroups- CRP guided therapy and 7 days antibiotic therapy. Results Out of 90 cases of suspected neonatal septicaemia antibiotics were stopped in ≤7 days in 61 cases (67.8%). In 25 out of 30 cases (27.8%) of neonatal septicaemia, antibiotics were stopped after 72 hours of initiation. In group II, antibiotics could be stopped in five days in 4 cases and remaining 26 cases antibiotics were given for 7 days. In group III, antibiotics could be stopped in 7 days in one case and remaining 29 cases antibiotics were given more than 7 days. Conclusions CRP has a high negative predictive value 96-100% and can be used as a marker of neonatal sepsis to reduce duration of antibiotics.